A case of idiopathic follicular mucinosis treated with bexarotene gel. (22nd August 2013) - Heyl, Jennifer; Mehregan, Darius; Kado, Jessica; Campbell, Michelle
Abstract Background Topical bexarotene 1% gel is currently FDA‐approved for early stage (IA and IB) persistent or refractory cutaneous T‐cell lymphoma (CTCL). No uniformly effective therapy exists for follicular mucinosis, although several treatments are routinely used. There are no known reports of topical bexarotene being used in the treatment of idiopathic follicular mucinosis when there is no association with CTCL. This article reports the first case of bexarotene gel to successfully treat persistent idiopathic follicular mucinosis. Materials and methods This study describes a 34‐year‐old Caucasian male with idiopathic follicular mucinosis. The patient had treatment failure with clobetasol 0.05% ointment and narrow‐band UVB. Intralesional injections with triamcinolone 5 mg/ml were successful for treating the plaques in the beard area. The patient was treated with bexarotene 1% gel applied twice a day to the persistent plaques on the lower extremities. The patient reported significant improvement in hair growth after only six weeks of treatment. The treatment was decreased to once a day due to erythema, and he had complete hair regrowth at 26 weeks. Discussion Several treatments have been described in the literature, such as corticosteroids, psoralen plus ultraviolet A (PUVA) light therapy, topical nitrogen mustard, and radiation therapy. Isolated cases have documented the beneficial responses of pimecrolimus, dapsone, indomethacin, minocycline, isotretinoin, hydroxychloroquine and interferons. No single treatment has been shown to be consistently effective. Conclusion Topical bexarotene 1% gel should be considered for patients with idiopathic follicular mucinosis resistant to standard treatment.